1995
DOI: 10.1007/bf01745076
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent thickening of the intima in aortocoronary saphenous vein grafts: Clinicopathological analysis of 24 patients

Abstract: The present study was undertaken to investigate histological changes in aortocoronary saphenous vein grafts (SVGs) and the relationship between intimal thickening of the SVGs and the interval after grafting. The SVGs were divided into five groups according to the degree of intimal thickening and associated luminal narrowing: minimal thickening (0%-10% stenosis), slight thickening (11%-25% stenosis), slight-to-moderate thickening (26%-50% stenosis), moderate thickening (51%-75% stenosis), and severe thickening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Despite extensive investigations in this field since the introduction of CABG in the late 1960s, only relatively few clinicopathological studies on causes of death and complications have yet been reported [6,16,18,29]. This may partly be explained by the fact that in the last decades the autopsy rate has shown continual declination in the western world.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Despite extensive investigations in this field since the introduction of CABG in the late 1960s, only relatively few clinicopathological studies on causes of death and complications have yet been reported [6,16,18,29]. This may partly be explained by the fact that in the last decades the autopsy rate has shown continual declination in the western world.…”
Section: Discussionmentioning
confidence: 78%
“…Morphological studies on changes after CABG have mainly been done on venous grafts [1,2,10,14,17,18,20,23,25,27,28,29]. It has been noted that damage of the endothelium of the graft [14], placement of a disproportionate graft on a small coronary artery [28], or distal anastomosis on an arteriosclerotically stenosed coronary artery segment with subsequent decreased flow [9] may result in occlusive thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…23) After angioplasty, the graft response varies in relation to the age of the graft. [23][24][25] In the first month, graft failure is usually due to thrombosis secondary to technical operative factors. In the first year, intimal thickening occurs.…”
Section: Discussionmentioning
confidence: 99%
“…14 Furthermore, the change in lumen diameter is modifiable. 15 IVUS and pathology studies have described an increase in SVG intima area 16 and adventitia 17 days to weeks after implantation. 4 Pathology studies have shown that differences in the wall thickness of grafts are predominantly caused by differences in thickness of the intima, rather than of the media or adventitia.…”
Section: Discussionmentioning
confidence: 99%